The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1038/bjc.1994.76
|View full text |Cite
|
Sign up to set email alerts
|

The 1993 Walter Hubert Lecture: the role of the p53 tumour-suppressor gene in tumorigenesis

Abstract: The p53 tumour-suppressor gene is mutated in 60% of human tumours, and the product of the gene acts as a suppressor of cell division. It is thought that the growth-suppressive effects of p53 are mediated through the transcriptional transactivation activity of the protein. Overexpression of the p53 protein results either in arrest in the G1 phase of the cell cycle or in the induction of apoptosis. Both the level of the protein and its transcriptional transactivation activity increase following treatment of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
203
1
14

Year Published

1995
1995
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(223 citation statements)
references
References 65 publications
5
203
1
14
Order By: Relevance
“…The recent demonstration that mouse ®broblasts with truncated BRCA2 are more sensitive to UV irradiation than controls (perhaps due to defective nucleotide or base excision repair) is clearly of interest in the context of this observation (Patel et al, 1998). Previous studies of sporadic breast cancer have revealed three codons at which mutation most commonly occurs: 175, 248 and 273 (Levine et al, 1994;Hollstein et al, 1994). Two BRCA1-associated and one BRCA2-associated tumour contained mutation at these`hot spot' codons, these being the tandem 247, 248 CC4TT mutation alluded to above in two cases and a single CGG4TGG transition at codon 248 in one BRCA1 tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The recent demonstration that mouse ®broblasts with truncated BRCA2 are more sensitive to UV irradiation than controls (perhaps due to defective nucleotide or base excision repair) is clearly of interest in the context of this observation (Patel et al, 1998). Previous studies of sporadic breast cancer have revealed three codons at which mutation most commonly occurs: 175, 248 and 273 (Levine et al, 1994;Hollstein et al, 1994). Two BRCA1-associated and one BRCA2-associated tumour contained mutation at these`hot spot' codons, these being the tandem 247, 248 CC4TT mutation alluded to above in two cases and a single CGG4TGG transition at codon 248 in one BRCA1 tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 tumor suppressor plays a crucial role in the maintenance of genomic stability by transcriptionally activating genes involved in DNA repair, growth arrest and apoptosis (Levine, 1997;Levine et al, 1994). P53 is activated by genotoxic agents and although the events involved in the activation of p53 are not well understood, the process is thought to be a complicated one, involving the stabilization of the protein (Kubbutat and Vousden, 1998), its translocation into the nucleus (Shaulsky et al, 1991b,c), and tetramerization (McLure and Lee, 1998), all of which are important steps in the process that lead to its activation for DNA binding and induction of target gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…p53 mutations are frequently found in human cancer (Hollstein et al, 1991) especially in association with progression or high grade malignancy (Carder et al, 1993). This is generally regarded as re¯ecting the importance, in the genesis of malignant clones, of by-passing the cell cycle constraints that facilitate repair or promote apoptosis (Levine et al, 1994) and so restrict the potential mutational impact of DNA damage. In line with this interpretation, mice de®cient in p53 by homologous recombination knockout are spontaneously highly susceptible both to leukaemia/lymphoma and solid tumours (Donehower et al, 1992;Purdie et al, 1994;Kemp et al, 1994) and progression of experimentally induced tumours is more rapid in the absence of p53 function (Kemp et al, 1993).…”
Section: Introductionmentioning
confidence: 99%